Postoperative complications of contemporary open and robot‐assisted laparoscopic radical prostatectomy using standardised reporting systems. (4th June 2018) - Pompe, Raisa S.; Beyer, Burkhard; Haese, Alexander; Preisser, Felix; Michl, Uwe; Steuber, Thomas; Graefen, Markus; Huland, Hartwig; Karakiewicz, Pierre I.; Tilki, Derya
Abstract : Objectives: To analyse time trends and contemporary rates of postoperative complications after radical prostatectomy (RP) and to compare the complication profile of open RP (ORP) and robot‐assisted laparoscopic RP (RALP) using standardised reporting systems. Patients and Methods: Retrospective analysis of 13 924 RP patients in a single institution (2005–2015). Complications were collected during hospital stay and via standardised questionnaire 3 months after, and grouped into eight schemes. Since 2013, the revised Clavien–Dindo classification was used ( n = 4 379). Annual incidence rates of different complications were graphically displayed. Multivariable logistic regression analyses compared complications between ORP and RALP after inverse probability of treatment weighting (IPTW). Results: After the introduction of standardised classification systems,  complication rates have increased with a contemporary rate of 20.6% (2013–2015). While minor Clavien–Dindo grades represented the majority (I: 10.6%; II: 7.9%), severe complications (Grades IV–V) were rare (<1%). In logistic regression analyses after IPTW, RALP was associated with less blood loss, shorter catheterisation time, and lower risk of Clavien–Dindo Grade II and III complications. Conclusion: Our results emphasise the importance of standardised reporting systems for quality control and comparison across approaches or institutions. Contemporary complication rates in a high‐volume centre remain low and are most frequently minor Clavien–Dindo grades. RALP had a slightly better complication profile compared to ORP.